2017
DOI: 10.1016/j.neuroimage.2016.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Functional circuit mapping of striatal output nuclei using simultaneous deep brain stimulation and fMRI

Abstract: The substantia nigra pars reticulata (SNr) and external globus pallidus (GPe) constitute the two major output targets of the rodent striatum. Both the SNr and GPe converge upon thalamic relay nuclei (directly or indirectly, respectively), and are traditionally modeled as functionally antagonistic relay inputs. However, recent anatomical and functional studies have identified unanticipated circuit connectivity in both the SNr and GPe, demonstrating their potential as far more than relay nuclei. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 86 publications
1
28
1
Order By: Relevance
“…Although average results suggested a small increase, no significant short-term (up to 9 min; Fig.6a) or long-term (up to 60 min; Fig.6b) effects were observed of turning on the stimulation. This is in apparent contrast to our previous results with cFos and also to a number of previously reported increases in BOLD or CBV responses in brain areas distant from various DBS (Albough et al, 2016;Chao et al, 2014;Lai et al, 2013;Van Den Berge et al, 2017;Young et al, 2011). However, we must…”
Section: Discussioncontrasting
confidence: 99%
“…Although average results suggested a small increase, no significant short-term (up to 9 min; Fig.6a) or long-term (up to 60 min; Fig.6b) effects were observed of turning on the stimulation. This is in apparent contrast to our previous results with cFos and also to a number of previously reported increases in BOLD or CBV responses in brain areas distant from various DBS (Albough et al, 2016;Chao et al, 2014;Lai et al, 2013;Van Den Berge et al, 2017;Young et al, 2011). However, we must…”
Section: Discussioncontrasting
confidence: 99%
“…The BOLD signal time courses were calculated for each ROI. One-way repeated measures ANOVA tests with Tukey post hoc analysis were conducted to evaluate frequency-dependent responses 10 . Significance level was set at *p < 0.05; **p < 0.01; ***p < 0.001.…”
Section: Methodsmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) represents a powerful tool for mapping brain activity on a whole-brain scale. Simultaneous DBS and fMRI (DBS-fMRI) thus could provide us with valuable insights into brain function and connectivity patterns, as well as modulatory effects and therapeutic mechanisms of functional electrical stimulation in various neurological disorders [8][9][10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent models provide a good way to elucidate the mechanisms involved and to optimize the stimulation target and paradigm. Using deep brain stimulation, it has been shown that high frequency (130Hz) stimulation in the external globus pallidus, substantia nigra or nucleus accumbens can transiently modulate brain-wide FC, particularly in downstream regions not directly activated by the stimulation (Albaugh et al, 2016;Van Den Berge et al, 2017). This indicates that high frequency neural oscillation could alter RSNs and the potential roles of those subcortical nuclei in shaping RSN activity.…”
Section: Manipulation Of Network By Brain Stimulationmentioning
confidence: 99%